Mechanical behavior of Al2O3-13%TiO2 ceramic coating at elevated temperature (2016)
The present thesis work has been carried out with the aim of studying the mechanical behavior of Al2O3-13wt.%TiO2 ceramic coating (AT-13) at room and elevated temperatures. AT-13 coatings were deposited, with two different standoff distances (110 and 140 mm), by the flame spraying technique; their microstructure and composition were analyzed by means of optical and scanning electron microscopy and X-ray diffraction. The mechanical behavior of the coated systems was evaluated by means of tensile tests, micro- and nano-indentation techniques; the critical strain for cracking was found to be between 0.7 and 0.51% for both coatings, it was obtained in situ and recorded with the aid of a high resolution camera during tensile test at room temperature, as well as the cracking stages A (initiation), B (nucleation), C (propagation), and D (saturation), represented on the stress-strain curve. The strains relative to the cracking stages (in situ) were applied to the coatings, at elevated (~200°C), and evaluated ex situ, finding that the AT-13 coating systems studied here were prone to delamination due to the poor strain compatibility between the substrate and the bond coat. It was found that the degree of porosity, highly influenced the critical strain which was higher for the coating with the lower porosity, Ɛ=0.70±0.08%, when compared to the coating with the higher porosity, Ɛ=0.51±0.05%.